2017
DOI: 10.1111/ppa.12658
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of isolates ofMagnaporthespp. from wheat and grasses infecting seedlings and mature wheat plants in Argentina

Abstract: Wheat blast of wheat (Triticum aestivum), caused by Magnaporthe oryzae pathotype triticum (MoT; anamorph Pyricularia oryzae) is a destructive disease in the South American countries of Brazil, Paraguay and Bolivia. In Argentina, the fungus was recently recorded on wheat and barley plants in the northeast part of the country, Buenos Aires and Corrientes Provinces, with a potential for spreading. This work aimed to study, for the first time, the morphocultural and pathogenic characteristics of Magnaporthe isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…There was no significant difference in the size of MoT conidia among the isolates tested. Furthermore, the size of conidia we isolated in Bangladesh was very similar with that from infected wheat fields of Brazil and Argentina (Castroagudin et al 2016;Perelló et al 2017). All of our isolates showed almost similar cultural and morphological characters indicating that the isolates probably originated from a single clade.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…There was no significant difference in the size of MoT conidia among the isolates tested. Furthermore, the size of conidia we isolated in Bangladesh was very similar with that from infected wheat fields of Brazil and Argentina (Castroagudin et al 2016;Perelló et al 2017). All of our isolates showed almost similar cultural and morphological characters indicating that the isolates probably originated from a single clade.…”
Section: Discussionsupporting
confidence: 74%
“…5236381.v1) also revealed that they belong to the same clonal type. Perelló et al (2017) reported that the growth of M. oryzae Triticum fungus was favored by temperatures ranging from 25 to 30°C in laboratory conditions. It has also been reported that the minimum and maximum temperatures required for the infection of wheat by MoT were 10°C and 32°C, respectively (Cardoso et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations